2006
DOI: 10.1021/ja056857j
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Au(I)-Catalyzed exo-Selective Cycloisomerization of Acetylenic Acids:  An Entry to Functionalized γ-Lactones

Abstract: A highly efficient gold-catalyzed cyclization reaction of various functionalized acetylenic acids is described. The cyclizations are conducted in the presence of Au(I) catalyst in acetonitrile at room temperature in a short reaction time. The reaction conditions are compatible with several functional groups, such as ester, alkene, alkyne, chloro, and free or protected alcohol, and lead to original gamma-lactones in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 254 publications
(85 citation statements)
references
References 27 publications
1
74
0
10
Order By: Relevance
“…Gold(I) was chosen for its easy handling ability and its lower sensitivity to moisture. The use of toluene, dichloromethane, or 1,2-dichloroethane led to the formation of the desired lactone in lower isolated yields (Table 1, entries [6][7][8]. The versatility of AuCl was then evaluated for other functionalized acid derivatives ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold(I) was chosen for its easy handling ability and its lower sensitivity to moisture. The use of toluene, dichloromethane, or 1,2-dichloroethane led to the formation of the desired lactone in lower isolated yields (Table 1, entries [6][7][8]. The versatility of AuCl was then evaluated for other functionalized acid derivatives ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…Various internal nucleophiles such as alkenyl, 2 sulfur-, 3 oxygen- 4 and nitrogen- 5 containing functions have been used in this regard. As part of our ongoing studies on metal-catalyzed atomeconomical reactions, 6 we have been interested in the use of gold for simple and highly efficient transformations. We have found that Au I catalyst promotes a highly efficient cycloisomerization of bis-homopropargylic diols under very mild conditions and in very short time.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this selectivity can be controlled by the choice of metal catalyst, as well as by careful design of the reaction conditions. Over the past years, numerous protocols based on transition-metals such as Rh, 6,7 Hg, [8][9][10][11] Ru, 12 Ag, [13][14][15] Au, [16][17][18][19] Cu 20,21 and Pd 6,14,[22][23][24][25][26][27][28] have been explored to allow for the synthesis of γ-alkylidene lactones. Unfortunately, most of these protocols require high catalyst loadings, prolonged reaction times, and/or elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…12 It is worth mentioning that this catalytic transformation provides an easy and atom-economical entry to enol-lactones, an important class of functionalized heterocycles useful as synthetic intermediates. Although a large number of catalysts able to convert γ-alkynoic acids into enol-lactones are already known, 13,14 most of the reported procedures require water-free reaction conditions. In fact, only a few examples, involving Pd-, 15 Pt-, 16 and Cu-based systems, 17 active in aqueous environments have been described to date in the literature.…”
mentioning
confidence: 99%